Achieving Transportation Equity: Meaningful Public Involvement to Meet the Needs of Underserved Communities. (April 2018) - Karner, Alex; Marcantonio, Richard A.
Civil rights and environmental justice laws and regulations aim to ensure fair processes and outcomes in regional transportation planning. Despite these requirements, people of color and low income tend to be disproportionately burdened while receiving few benefits. We argue that a key factor driving this disconnect is the nature of public involvement, in particular, a near-absence of meaningful public involvement through which affected residents can influence and shape decisions. We propose a new model for public involvement in transportation planning, based on a review of the literature and two policy and planning case studies. Our model identifies addressing the priority unmet needs of underserved communities as a fundamental touchstone of equity and argues for dedicating a stream of funding to meet those needs. Widespread application of this model, at the regional level and elsewhere, would likely result in improvements to both the general welfare and transportation equity conditions.